Female silence in K.S. Maniam’s play the sandpit: a monologue - Wan Roselezam bt. Wan Yahya, (Penerbit UKM, 2003)
This paper explores the concept of female silence in K.S. Maniam’s play The Sandpit: A Monologue . It is his portrayal of the mental conflict of his female protagonist as a result of a polygamous marriage in a working-class Indian family. Maniam uses the monologue to convey his protagonist’s various emotions and thoughts which could not have been presented adequately if conveyed in dialogue form. The silence and passivity of Santha is seen as active when viewed using this paradigm of female silence (a feminist criticism) because the silences are strategies used by her to resist the oppressive social roles prescribed by her traditional Indian customs. The isolation of Santha from the beginning to the end of her monologue is, of course, in keeping with the traditional role and place of women in Indian society, which the playwright seems to view as the acceptable female condition in a patriarchal society. Maniam’s conclusion seems to exalt the suffering, sacrificing, submissive wife, since it is through these qualities that she will not only survive, but finally triumph.